Hydrodynamics of gas-liquid slug flow along vertical pipes in the laminar regime - Experimental and simulation study - T. S. Mayor (2007)
An experimental and simulation study on free-bubbling vertical slug flow in the laminar regime was developed. A non-intrusive image analysis technique and a developed simulation code (SFS, slug flow simulator) were used for the purpose. A single correlation was obtained for the prediction of the bubble velocity as a function of the length of the liquid slug ahead of the bubble. Strong bubble interaction was found for liquid slugs shorter than 2D, with weak and decreasing interaction persisting for longer liquid slugs. Coalescence, though sparse, was found to occur along the whole column length (6.5 m). These observations differ from the findings regarding turbulent regime (bubble interaction for liquid slugs shorter than 8-10D and coalescence mainly in the lower part of the column). A slug flow entrance length of 70-100D was obtained for inlet slug length distributions centered on 2-4D, for the ranges of superficial gas and liquid velocities studied (0.05-0.20 m/s). Different inlet slug length distributions (for instance centered on 2D and 5D) were found not to evolve to a single flow pattern within the 6.5 m length of the column. General expressions were proposed to predict the evolution of the mode and standard deviation of bubble velocity, bubble length, and liquid slug length distributions as a function of the vertical column coordinate and superficial gas and liquid velocities. Bubble coalescence was found to govern the evolution of the liquid slug length along the column. Gas expansion and bubble coalescence were found to play important roles in the evolution of bubble length and velocity.